Engaging general population: Vaccine confidence, communication and mandatory law. (30th September 2020) - Lopalco, P L
Abstract: Hesitancy is defined as the reluctance or refusal to be vaccinated even in case of vaccine availability and is included by the WHO among the top ten threats to global health. Vaccine confidence is an essential component of the hesitancy. Fear of adverse events and lack of trust in vaccine efficacy discourage the public and drive them toward the choice of refusal. Misinformation and lack of effective communication strategies may seriously jeopardize vaccination programmes. Providing effective communication requires specific competencies that often are not part of the common core competencies of those involved in vaccination programmes. In particular, the rapid evolution of the communication environment due to novel technologies makes the task even more difficult. The general population in order to comply with the official vaccine recommendation throughout the life course is therefore a complex task. In the presence of worrying signals of lack of vaccine confidence, public health decision can be driven by emergency decisions rather than investing in mid-terms communication programmes. Vaccination mandates are public health measures that are proven to be effective in increasing vaccine uptake. Increasing anti-vaccine sentiment may be a potential negative trade-off. For this reason, the introduction of vaccination mandates should be combined with a structured communication strategy. In addition, vaccine sentiment should be actively monitored when any change in vaccine offer policy is implemented.